EVALUATION OF OCCUPATIONAL HEALTH AND SAFETY MANAGEMENT SYSTEM PERFORMANCE INDICATORS WITH AHP - Abdullah YILDIZBAŞI (Fırat University, 2019)
Nowadays, both in the world and in Turkey, businesses tend to work more consciously on occupational health and safety. Since a good Occupational Health and Safety (OHS) system will increase production efficiency due to work efficiency. OHS aims to ensure that working conditions in the workplace are carried out in health and safety and those employees are physically and mentally protected from the hazards that may arise during work and provide legal, technical and medical precautions in the workplace in line with this goal. The OHS Management System is used to help businesses achieve their goals and to ensure that health and safety work is compatible with the overall strategy of the business. Frequent evaluation of the system's performance is crucial to the effectiveness and efficiency of the business. In this study, the performance criteria of the Occupational Health and Safety Management System are considered. Firstly, 80 performance indicators to be evaluated by examining OHSAS-18001 and ISO 45001 Management Systems have been determined. These are summarized in 5 main sections as Policy, Organization, Planning and Implementation, Evaluation. Then these performance indicators were evaluated together with experts who were working in the field of Occupational Health and Safety and who were defined as Decision Makers in the study and numerical data were obtained through the binary comparison surveys. Key performance indicators were determined by evaluating the numerical data obtained using the AHP method. As a result, using the AHP method, rather than using all of the 80 performance indicators set for the Occupational Health and Safety Management System performance measurement, the feasibility of performance measurement with the key performance indicators obtained has been examined.